Plant-microbe interactions of selenium hyperaccumulators: effects on plant growth and selenium metabolism - Lindblom, Stormy Dawn, author; Pilon-Smits, Elizabeth, advisor; Leach, Jan, committee member; Wangeline, Ami, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: hyperaccumulator; microprobe; plant-microbe; rhizobia; rhizosphere; selenium